2020
DOI: 10.21203/rs.3.rs-131071/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability of Government Measures Against Covid-19 Pandemic in Senegal: a Mixed Methods Study

Abstract: Background: While the first case of COVID-19 was declared on March 2 2020 in Senegal, the government banned the attendance of places of worship on 14 March. On March 23, it introduced a curfew, a ban on movement between regions, and the closure of markets. These measures were lifted in May and June 2020. The objective of this study is to measure and understand the acceptability of these four governmental measures as well as the level of public trust in the state to fight the pandemic. Methods: We carried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Hesitancy and refusal to be vaccinated were related to living in large cities (Dakar, Thiès, and Diourbel). These same perceptions were noted in our previous study, which showed that the more regions are affected by the pandemic, the less confidence respondents have in the government and the less effective they perceive the measures to be [22]. As of December 2, 2021, these three most populated regions of Senegal will account for more than 80% of the cases of COVID-19 in the entire country [18].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Hesitancy and refusal to be vaccinated were related to living in large cities (Dakar, Thiès, and Diourbel). These same perceptions were noted in our previous study, which showed that the more regions are affected by the pandemic, the less confidence respondents have in the government and the less effective they perceive the measures to be [22]. As of December 2, 2021, these three most populated regions of Senegal will account for more than 80% of the cases of COVID-19 in the entire country [18].…”
Section: Discussionsupporting
confidence: 78%
“…The study population consisted of individuals from the general population living in Senegal aged 18 years and older with a mobile phone number. In June 2020, we conducted an initial nationwide telephone survey of 813 people to measure the social acceptability of governmental measures to control COVID-19 [22]. The study used a marginal quota sampling strategy [23].…”
Section: Methodsmentioning
confidence: 99%
“…Elsewhere in West Africa, 35.6% of respondents put total trust in those in charge of health to manage the pandemic, and 34.6% had moderate trust in them [36]. In Senegal, acceptability of government measures was higher but heterogeneous according to the individual concerned [37]. In effect, people consider the curfew to be more important (85.7%) than the closure of places of worship (55.4%).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more educated individuals were less in favour of curfew acceptability. Although the curfew is appreciated for its qualitative aspects related to security with the reduction in attacks and social / family cohesion with a significant time spent with the family [49] , we could think that its restrictive conditions of individual freedoms could be at the origin of its opposition among the educated population [50] . These results were consistent with France regarding attitudes towards restrictive measures [51] .…”
Section: Discussionmentioning
confidence: 99%